THE REALIZATION OF THE INTELLECTUAL SYSTEM OF FINANCIAL PROGNOSTICATION (Journal of Information Technologies in Education (ITE), 2012)
The article describes the realization mechanism of intellectual tasks block in the integration system of financial prognostication. The problem of informational and communicational strategic partnership is actualizing between market participants, governing authorities and society.
Keywords: data meaning; financial forecasting; integrated system